Development and design of ultra-high ductile magnesium phosphate cement-based composite using fly ash and silica fume. (March 2023) - Feng, Hu; Liang, Junhao; Guo, Aofei; Lv, Lijun; Sun, Zhihui; Sheikh, M. Neaz; Liu, Fengjuan
Abstract: Magnesium phosphate cement (MPC) is one of the most promising binders to partially replace Portland cement to reduce carbon emissions. This study attempted to develop and design an ultra-high ductile MPC-based composite (UHDMC) using fly ash (FA) and silica fume (SF). Firstly, the macro-mechanical analysis of the UHDMC indicated that both the ultimate tensile stress and the ultimate tensile strain improved greatly when the additions of FA and SF replacing MPC were 30% and 20%, respectively. Compared to the addition of SF, the addition of FA resulted in a lower ultimate tensile stress but a higher ultimate tensile strain of UHDMC. Secondly, the micro-mechanical properties of the UHDMC were examined, and the stress-based and energy-based pseudo strain hardening indices ( PSH σ and PSH J, respectively) were calculated. It was found that both PSH σ and PSH J of the UHDMC increased as the addition of SF or FA contents replacing MPC increased. Compared to the addition of SF, the addition of FA resulted in a similar PSH σ but a higher PSH J . A quantitative relationship between pseudo strain hardening indices and ultimate tensile strain was established to guide the design of UHDMC with a desired ultimate tensile strain. It was found that PSH σ and PSH J should reach above 2.2 and 26.7 concurrently for the UHDMC with ultimate tensile strains up to and above 3%. Lastly, the microanalysis was conducted to reveal the influence mechanism of FA and SF on the UHDMC. This study provides some technical guidance on the development and optimal design of UHDMC.